Pengaruh Catcalling terhadap Self Esteem pada Mahasiswi - Surya Ningtyas, Darmayanti Yuliana; Ervina, Iin; Istiqomah (Indonesian Journal Publisher, 2024)
Self-esteem is an individual's evaluation in assessing or viewing himself regarding his abilities. One of the things that can cause self-esteem to decrease is catcalling behavior. Catcalling is the expression of sexually oriented words aimed at the victim using verbal and non-verbal expressions which often occurs in public places. This research aims to determine the effect of catcalling on self-esteem among female students in Jember Regency, and the impact experienced by victims is that they will always feel like they are blaming themselves, lack of self-confidence, low self-esteem. The subjects of this research are students from UNMUH Jember, UNEJ, POLIJE, and UIN KHAS In Jember, 348 people have experienced catcalling behavior in the last year. This research uses quantitative methods. Researchers used the Issac table formula to determine the sample size. The data analysis methods used in this research are validity test, reliability test, linearity test, and regression analysis test. The scale used in this research is the result of modifications using the Street Harassment Scale and the Self Esteem Scale. The results of this research show that the calculated F value is 0.163 > 0.0028 and the significance value is 0.686 > 0.05, which means that H0 is rejected and Ha is accepted, which means there is no significant influence between the catcalling variable and the self-esteem variable. For an R Square value of 0.000. This means that the catcalling variable has an influence of 0% on the self-esteem variable or it could be said that the catcalling variable has no influence on the self-esteem variable. This means that there are other variables that may influence self-esteem.